Analisis Feminisme Dalam Lirik Lagu "Kuat" Karya Thavita - Natasya Al Fadila Z (Literasi: Jurnal Pendidikan Guru Indonesia, 2024)
The aim of this research is to examine the lyrics of Thavita's "strong" song which depicts women's empowerment. The lyrics of this song describe women's resistance to gender equality which often occurs in various parts of their lives. This song is a medium to emphasize the resilience and courage of women in facing life's challenges and supporting other women using qualitative descriptive research methods. The lyrics of this song talk about women's resistance and empowerment as well as their struggle against gender injustice and their right to life. In addition, the story in this song can encourage women to take control of their own lives, respect fellow humans, and succeed without being limited by the standards set by a patriarchal society. This song emphasizes the role of women in building a more just and equal world through lyrics that contain an inspirational message.